F STRUKTUR BAHASA IJAB KABUL DAN RASIONALITAS LINGUISTIK DALAM PERNIKAHAN: IJAB DAN KABUL PERNIKAHAN DALAM PERNIKAHAN SANGAT KONDISIONAL - fatawi fatawi (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2025)
This study examines the linguistic structure of ijab-qabul in the marriage contract and its implications for marital validity from the perspectives of Islamic law and linguistics. Differences between the syntactic systems of Arabic and Indonesian frequently give rise to debates concerning the order of subject and object in the sighat of the marriage contract. Employing a qualitative normative approach supported by limited empirical data, this study analyzes classical and contemporary Islamic jurisprudence alongside Ferdinand de Saussure’s structural linguistic theory to elucidate the function of language as a social system (langue). The findings indicate that variations in the linguistic structure of ijab-qabul do not affect the validity of the marriage contract, provided that its pillars and conditions are fulfilled and the intent of the contract is clearly understood. The Islamic legal principle al-‘ibrah fi al-‘uqūd bi al-maqāṣid wa al-ma‘ānī, which holds that legal consideration in contracts is based on objectives and meanings rather than literal expressions-underscores the primacy of substantive intent over linguistic formalities. Nevertheless, within the framework of contemporary Islamic law, clear and verifiable linguistic formulations remain necessary to ensure legal certainty and protection.